EFEKTIVITAS PEMBELAJARAN BAHASA ARAB DENGAN METODE EXPERIENTIAL LEARNING MENGGUNAKAN KITAB MATAN AL-JURUMIYAH DI SMP IT FATHONAH PALEMBANG (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of the Experiential Learning method based on the Matan Al-Jurumiyah book in enhancing reading skills (maharah qirā’ah) and critical thinking abilities in Arabic language learning at SMP IT Fathonah Palembang. A quantitative approach was employed using a quasi-experimental design of the Nonequivalent Control Group Design type. The study sample consisted of two classes, namely an experimental class and a control class, each comprising 30 students selected through purposive sampling. The research instrument was an objective test consisting of 25 multiple-choice questions, administered in both pre-test and post-test formats. Data were analyzed using SPSS version 26 through three statistical stages: the normality test (Shapiro-Wilk), the homogeneity test (Levene’s Test), and the Independent Sample t-Test. The normality test results showed that the data in both classes were normally distributed, while the homogeneity test indicated equal variance across groups. The t-test analysis produced a significance value (Sig. 2-tailed) of 0.001 (< 0.05), indicating a statistically significant difference in learning outcomes between the experimental and control groups. The post-test mean difference suggests that the Experiential Learning method positively impacts students’ reading and critical thinking skills in Arabic. In conclusion, the implementation of the Experiential Learning method using the Matan Al-Jurumiyah book is proven effective in improving Arabic learning outcomes among junior high school students. These findings suggest that experience-based learning approaches can serve as innovative strategies in foreign language instruction.